2000
DOI: 10.1093/emboj/19.19.5051
|View full text |Cite
|
Sign up to set email alerts
|

A short sequence in the N-terminal region is required for the trimerization of type XIII collagen and is conserved in other collagenous transmembrane proteins

Abstract: The recombinant transmembrane protein type XIII collagen is shown to reside on the plasma membrane of insect cells in a 'type II' orientation. Expressions of deletion constructs showed that sequences important for the association of three alpha1(XIII) chains reside in their N- rather than C-terminal portion. In particular, a deletion of residues 63-83 immediately adjacent to the transmembrane domain abolished the formation of disulfide-bonded trimers. The results imply that nucleation of the type XIII collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 38 publications
4
105
0
Order By: Relevance
“…Both transmembrane collagens XIII and XVII are proteolytically released from cell surface to the extracellular matrix (7,8,31), which allows them to function as matrix proteins, contributing to cell adhesion and migration. We have recently shown that the ␣ 1 ␤ 1 integrin, rather than ␣ 2 ␤ 1 , is a cellular receptor for type XIII collagen (17).…”
Section: Discussionmentioning
confidence: 99%
“…Both transmembrane collagens XIII and XVII are proteolytically released from cell surface to the extracellular matrix (7,8,31), which allows them to function as matrix proteins, contributing to cell adhesion and migration. We have recently shown that the ␣ 1 ␤ 1 integrin, rather than ␣ 2 ␤ 1 , is a cellular receptor for type XIII collagen (17).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fibrillar collagens and type IV collagen require the presence of globular sequences C-terminal to the triple-helical domain to initiate chain registration (3-5, 32). However, trimerization of type XII collagen is dependent on specific post-translational modifications of the collagen domain (33), whereas chain association of the membraneassociated collagen, type XIII, occurs in the N-terminal region (34). Refolding experiments on collagen type III indicated that interchain disulfide bridges at the C terminus of the triple helix were sufficient to function as a nucleus for the refolding of the triple helix (6).…”
Section: Cooperativity Exists Between the Iia Nh 2 -Propeptide Collagmentioning
confidence: 99%
“…In accordance with a previous report (18), CLAC formed dimers and trimers even though the splice variant expressed in this study lacks parts of the sequences of the COL3 and NC4 domains (residues 589 -640, according to the numbering of GenBank TM /EBI accession number AF293341). Multimer formation has also been observed with a COL3 and NC4 domain-truncated collagen XIII protein, indicating that the C-terminal domains of these collagens are not critical for chain association (40). The majority of CLAC isolated from human AD brain is in a monomeric or dimeric form; a trimeric form is rarely observed.…”
Section: Discussionmentioning
confidence: 99%